Review on alternative energy education in Malaysia - Sahriah Basri,; Siti Umaira Zakaria,; Siti Kartom Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Alternative energy sources have gained increasing attention due to the diminishing fossil fuel reserve. However, awareness of the importance and use of this alternative energy is still lacking in developing countries, especially in Malaysia. Alternative energy technology is also not widely known amongst students. Community awareness of the importance and usability of alternative energy to ensure the preservation of the earth and nature remains less due to the convenience of the community to existing power sources from fossil fuel. The dependence on fossil fuel has contributed to 40% of the carbon dioxide emission damaging the ecosystem and will undoubtedly have adverse effects in the future. Hence, replacing this energy source with alternative sources is necessary to preserve the environment. To increase public awareness regarding this issue, scholars should create an application that would be easily accessible to the society. This study aims to criticise public's awareness and challenges faced in educating the community on alternative energy. Society awareness is important in maintaining and preserving the environment because alternative energy sources are eco-friendly and produce less carbon dioxide than existing energy resources. This article also examines the development of education modules for students especially in Malaysia. Additionally, a curriculum oriented in higher education is recommended to produce a generation that loves nature and explores the environment with the development of science and technology. Comparisons of education systems among developed countries are helpful in achieving this objective.